2017
DOI: 10.1097/inf.0000000000001614
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Lesions in Congenital Toxoplasmosis in Santa Isabel do Ivaí, Paraná, Brazil

Abstract: We verified clinical and psychopedagogic aspects of congenital cases with ocular sequelae, 13 years after toxoplasmosis outbreak in Santa Isabel do Ivaí, and current seroprevalence of this zoonosis in pregnant women. Audiologic and ophthalmologic evaluations were performed in congenital cases, in addition to collection of clinical and psychopedagogic data. In pregnant women, current seroprevalence was observed. Among affected teenagers, 2 of 5 are behind in school grade, and 4 of 5 reported learning difficulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…The municipality of Santa Isabel do Ivaí, Paraná has a human population of less than 10,000. A large outbreak of toxoplasmosis was reported from this town; this outbreak has been the source of great social, economic, medical concern and debate [20][21][22]. In November 2001, a local physician requested serological tests to diagnose dengue, mononucleosis, cytomegalovirus infection, hepatitis, and toxoplasmosis, and two persons were found seropositive for T. gondii IgM and IgG antibodies.…”
Section: Santa Isabel Do Ivaí Paranámentioning
confidence: 99%
See 2 more Smart Citations
“…The municipality of Santa Isabel do Ivaí, Paraná has a human population of less than 10,000. A large outbreak of toxoplasmosis was reported from this town; this outbreak has been the source of great social, economic, medical concern and debate [20][21][22]. In November 2001, a local physician requested serological tests to diagnose dengue, mononucleosis, cytomegalovirus infection, hepatitis, and toxoplasmosis, and two persons were found seropositive for T. gondii IgM and IgG antibodies.…”
Section: Santa Isabel Do Ivaí Paranámentioning
confidence: 99%
“…New lesions were seen 1 year after the initial outbreak [21,39]. Ten women seroconverted during pregnancy; one of these had a spontaneous abortion and three escaped congenital infection [22]. Six babies were born with congenital toxoplasmosis; one died at 9 months of age despite anti-T. gondii therapy.…”
Section: Santa Isabel Do Ivaí Paranámentioning
confidence: 99%
See 1 more Smart Citation
“…Parasite genotypes seem to play a role in the virulence of human infections 14 , and it was demonstrated that a higher prevalence of non-archetypal T. gondii strains increase the risk of ocular manifestations of the disease 35 . Sanders et al 8 , in the same study area, reported learning difficulties and high ocular impairment in children who were infected in the third trimester of pregnancy. These facts contributed to the finding in the present study of pregnant women with recurrent retinochoroiditis and impaired immune systems.…”
Section: Discussionmentioning
confidence: 87%
“…If transmission occurs in the third trimester, neurological lesions may be absent but some infected newborns present with subclinical infection and they are at risk of developing ocular lesions at any time 4 , 5 . In South America, 70-80% of children infected in the second and third gestational trimesters frequently develop important classical or atypical recurrent eye injury as a result of chorioretinitis 7 , 8 . This fact is attributed to the parasite genotypic diversity present in this region, including clonal lineages with high virulence 9 , 10 12 .…”
Section: Introductionmentioning
confidence: 99%